Reimagining the coach-athlete-environment relationships in the digital communications era - Taylor, S.; Renshaw, I.; Pinder, R.; Polman, R.; Davids, K.; Gorman, A. D. (International Sport Coaching Journal, 2025)
The evolution of 4G and 5G digital technologies is (re)shaping contemporary methods of coaching by removing the requirement for coaches to be physically present at practice and competition venues. This technological advance provides opportunities for sports organisations, especially those with limited resources, to implement innovative learning and performance solutions by delivering remote coaching. In this insight paper, we reimagine what "the coaching environment" could look like by considering how the remote context may shape coaching. Currently, there is limited understanding of the use and implementation of such approaches, highlighting a need for further research to be conducted to better understand how online environments may impact the coaching process. We propose how adopting an ecological dynamics approach may align with existing research within coaching science and contemporary theorising in skill acquisition and motor learning, advocating a learner-centred approach to coaching. We then introduce and discuss the work of Roger Barker with a focus on "behaviour settings" and how this perspective may provide a lens for future research to explore different coaching environments. When complemented by ethnographic methodologies, this approach may provide a novel way to understand how coach-athlete interactions are framed in situ.